To What Extent Do Macroeconomic Factors Affect Companies’ Performance? - Chen, Yin-An (2010)
The main purpose of this study is trying to explore whether the macroeconomic factors will affect corporate performance or not in the UK. Therefore, my study randomly chooses 50 companies from FTSE 350 as the sample dataset for examining the relationship between 10 macroeconomic variables and firm’s performance. Also, there are two models used in my study as the measurements of corporate performance which is based on firm’s market returns (Tobin’s q) and accounting returns (ROA). On the base of using SPSS, the results present that change of 20 years bond yield, change of industrial productivity index (IPI), and change of gross domestic product (GDP) have positively significant effect on firms’ market and accounting returns. On the other hand, the change of oil price reports a negative relation with companies’ market and financial performance. Moreover, change of M0 and M4 present a positive relationship with companies’ market returns and change of unemployment rate has a positive impact on firms’ accounting returns. However, there are three macroeconomic variables, change of exchange rate, change of consumer price index (CPI), and yearly rediscount rate, have no significant effect on firms’ market and accounting performance.